The Influence Of Ambassador's Brand On Brand Image And Their Impact On Buying Interest Of Tokopedia Consumers - Firsan Nova (Politeknik APP Jakarta, 2022)
This study aimed to determine the effect of brand ambassadors on buying interest through the brand image in Tokopedia e-commerce and using primary data from the distribution of questionnaires from 210 respondents domiciled in East Jakarta who uses Tokopedia. Samples were taken using purposive sampling and determining the number of samples using quota sampling. The analysis test was carried out using Structural Equation Modeling (SEM) and processing using LISREL ver. 8.8. The results showed that the influence of brand ambassadors through the brand image on buying interest in e-commerce Tokopedia was positive, or there was a significant relationship. Based on these results, it can be said that brand image as an intervening variable has a positive influence or has a significant relationship.